2016
DOI: 10.1021/acs.biochem.6b00658
|View full text |Cite
|
Sign up to set email alerts
|

Succinyl-5-aminoimidazole-4-carboxamide-1-ribose 5′-Phosphate (SAICAR) Activates Pyruvate Kinase Isoform M2 (PKM2) in Its Dimeric Form

Abstract: Human pyruvate kinase isoform M2 (PKM2) is a glycolytic enzyme isoform implicated in cancer. Malignant cancer cells have higher levels of dimeric PKM2, which is regarded as an inactive form of tetrameric pyruvate kinase. This perceived inactivity has fueled controversy over how the dimeric form of pyruvate kinase might contribute to cancer. Here we investigate enzymatic properties of PKM2G415R, a variant derived from a cancer patient, which we show by size-exclusion chromatography and SAXS to be a dimer that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…To identify residues that mediate the interaction between the Phe and FBP allosteric mechanisms, we analysed changes imposed by FBP binding on PKM2 dynamics. MD simulations of PKM2 apo and PKM2 FBP , corroborated by IM-MS data, indicated that the protein does not undergo large conformational changes, in agreement with previously published smallangle X-ray scattering (SAXS) experiments that showed no FBP-driven change in the radius of gyration of PKM2 tetramers 36 . This suggested that ligand-induced conformational changes are likely limited to subtle backbone re-arrangements and side-chain motions.…”
Section: Allohubmat Reveals Residues That Mediate a Cross-talk Betweesupporting
confidence: 89%
See 2 more Smart Citations
“…To identify residues that mediate the interaction between the Phe and FBP allosteric mechanisms, we analysed changes imposed by FBP binding on PKM2 dynamics. MD simulations of PKM2 apo and PKM2 FBP , corroborated by IM-MS data, indicated that the protein does not undergo large conformational changes, in agreement with previously published smallangle X-ray scattering (SAXS) experiments that showed no FBP-driven change in the radius of gyration of PKM2 tetramers 36 . This suggested that ligand-induced conformational changes are likely limited to subtle backbone re-arrangements and side-chain motions.…”
Section: Allohubmat Reveals Residues That Mediate a Cross-talk Betweesupporting
confidence: 89%
“…This idea resonates well with findings from MD simulations indicating that dynamic coupling between distal sites upon FBP binding can occur in the PKM2 protomer, and suggest that allostery is encoded in the protomer structure [70][71][72] . Furthermore, a patient-derived PKM2 mutant (G415R) occurs as a dimer that can bind to FBP but cannot be activated and does not tetramerise 36 . Moreover, SAICAR can activate PKM2(G415R) dimers, in the absence of tetramerisation 36 .…”
Section: Allohubms Reveal Insights Into the Relationship Between Pkm2mentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is the only step within the pathway that has been shown to be reversible, suggesting that there may be a level of regulation yet to be explored. SAICAR was identified as an allosteric regulator of the cancer-specific pyruvate kinase isoform M2 under glucose limited conditions (Figure 1) [26-28]. These observations provide a glimpse into the interconnectivity of metabolic pathways in response to the bioenergetics and biosynthetic requirements of the cell.…”
Section: Purine Metabolismmentioning
confidence: 99%
“…Pathway cofactor, 10-formyltetrahydrofolate (10-fTHF) is a product of one-carbon metabolism (denoted with a *, for biosynthetic pathway see Figure 3). Intermediate SAICAR was shown to allosterically activate pyruvate kinase isoform M2 (PKM2, EC 2.7.1.40) in glycolysis (red) [26-28]. AICAR is also a byproduct of histidine biosynthesis (purple).…”
Section: Figurementioning
confidence: 99%